2015
DOI: 10.1111/jgs.13665
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cognitive Impairment and Chronic Kidney Disease in Mexican Americans

Abstract: ObjectivesTo analyze the association between chronic kidney disease (CKD) and mild cognitive impairment (MCI) in Mexican Americans and to determine whether there is a blood‐based proteomic profile linking CKD to MCI.DesignRetrospective analysis of cohort study.SettingHealth and Aging Brain among Latino Elders study.ParticipantsMexican Americans (N = 437, 105 men, 332 women).MeasurementsData were analyzed to examine the link between estimated glomerular filtration rate (eGFR) and detailed neuropsychological fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
0
23
0
6
Order By: Relevance
“…Samples were analyzed from the Health & Aging Brain among Latino Elders (HABLE) study, an ongoing epidemiologic study of cognitive aging among community‐dwelling Mexican Americans and non‐Hispanic whites [21,22]. The HABLE study uses a community‐based participatory research approach, which involves partnering communities to conduct studies of human disease.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed from the Health & Aging Brain among Latino Elders (HABLE) study, an ongoing epidemiologic study of cognitive aging among community‐dwelling Mexican Americans and non‐Hispanic whites [21,22]. The HABLE study uses a community‐based participatory research approach, which involves partnering communities to conduct studies of human disease.…”
Section: Methodsmentioning
confidence: 99%
“…Moderate eGFR (45-59mL/min/1.73m 2 ) and high eGFR (≥60mL/min/m 2 ) were not associated with cognitive function. In the Health and Aging Brain among Latino Elders study (23), 437 Mexican Americans with low eGFR (<45 mL/min/1.73m 2 ) showed poorer global cognitive function as well as poorer processing speed, executive function, and visuospatial skills than individuals with moderate (45-59 mL/min/1.73m 2 ) or high (≥60 mL/min/1.73m 2 ) eGFR. In another study, Event Related Potentials (ERPs) were used to measure speed of cognitive processing in individuals with CKD and ESRD; the authors found significant prolongation of P3 latencies (corresponding to slower processing speed) in CKD stages 4 and 5 (17).…”
Section: Cognitive Impairment In Ckdmentioning
confidence: 99%
“…Although cognitive impairment is well studied in CKD, only three studies (12, 19, 23) to our knowledge have assessed MCI as an outcome. In their study, Post et al (19) studied 24 patients with CKD and 27 patients with ESRD receiving hemodialysis (HD) without any history of dementia, stroke or neurodegenerative disease.…”
Section: Cognitive Impairment In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from 381 participants from the Health and Aging Brain among Latino Elders (HABLE) study were analyzed (Edwards et al ., 2015 ; Johnson et al ., 2015a; Szerlip et al ., 2015 ). The HABLE study is an ongoing epidemiological study of cognitive aging among community-dwelling Mexican-American individuals.…”
Section: Methodsmentioning
confidence: 99%